AZNAR, H., ALONSO, E. y MENÉNDEZ, M. (eds.) (2018), Ortega y el tiempo de las masas, Madrid: Plaza y Valdés. - Vilarroig Martin, Jaime (Daimon Revista Internacional de Filosofia, 2019)
Reseña de: AZNAR, H., ALONSO, E. y MENÉNDEZ, M. (eds.) (2018), Ortega y el tiempo de las masas, Madrid: Plaza y Valdés.